A method for selectively degrading resistance genes in water by electrochemical oxidation
By loading carbon nanotubes and ethylene end group modification on the glassy carbon electrode and combining it with molecular imprinting technology, an electrode that can specifically identify resistance genes was prepared, which solved the problem of non-selective resistance gene removal in the existing technology and achieved efficient electrochemical oxidation degradation.
Patent Information
- Application Number
- CN202411400638.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The electrochemical oxidation method in the existing technology lacks selectivity for removing resistance genes and is easily affected by other chemical pollutants, resulting in poor removal effect.
A glassy carbon electrode loaded with molecular imprinting was used as the anode. Through carbon nanotube loading and ethylene end group modification, combined with molecular imprinting technology, an electrode that can specifically recognize and bind to resistance genes was prepared, and degraded during the electrochemical oxidation process.
It achieves efficient and selective removal of resistance genes in water, improves the degradation effect of resistance genes, and solves the problem of easy detachment of molecular imprinting on the electrode surface.
Smart Images

Figure CN119143250B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollutant degradation, and in particular to a method for selectively degrading resistance genes in water by electrochemical oxidation. Background Art
[0002] Excessive or inappropriate use of antibiotics can induce pathogenic bacteria to develop antibiotic resistance genes (ARGs). These genes can spread through horizontal gene transfer (HGT), posing a serious threat to public health and considered a new type of environmental pollutant. In 2019, 4.95 million deaths worldwide were linked to bacterial resistance. Current water treatment processes are ineffective in removing these resistance genes.
[0003] In the existing technology, treatment methods including electrochemical oxidation are not selective for the removal of resistance genes and are easily affected by other chemical pollutants, resulting in non-selective removal of ARGs. Therefore, it is necessary to improve the selective removal of resistance genes. Summary of the Invention
[0004] In order to solve the above problems, the present invention provides a method for selectively degrading resistance genes in water by electrochemical oxidation.
[0005] In a first aspect, the present invention provides a method for selectively degrading resistance genes in water by electrochemical oxidation, comprising:
[0006] With the first electrode as an anode and the second electrode as a cathode, an electric current is applied to degrade the resistance gene in the water body;
[0007] Wherein, the first electrode is a molecularly imprinted glassy carbon electrode;
[0008] The molecularly imprinted glassy carbon electrode is obtained by loading a glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and loading the molecular imprint. The molecular imprint is used to selectively identify resistance genes from chemical pollutants in water and bind to the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria.
[0009] Description: Through the above method, the glassy carbon electrode is used as the anode and the second electrode as the cathode, and current is applied to degrade the resistance genes in the water. Molecular imprinting technology is coupled with electrochemical oxidation to prepare a glassy carbon electrode loaded with DNA molecular imprinting. The glassy carbon electrode can specifically identify and bind to the target resistance gene in the electrochemical reaction and degrade it through the electrochemical oxidation process. This method combines the high selectivity of molecular imprinting and the strong oxidizing ability of electrochemical oxidation to achieve efficient and selective removal of resistance genes in water.
[0010] Furthermore, the method of loading the glassy carbon electrode with carbon nanotubes includes:
[0011] The glassy carbon electrode was placed in a carboxylated carbon nanotube dispersion and deposited at a set voltage of -1 to -1.2 V for a deposition time of 1000 to 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode.
[0012] The carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent, and the concentration of the carboxylated carbon nanotube dispersion is 0.02-0.05 mg / mL.
[0013] Note: By loading carbon nanotubes on glassy carbon electrodes, electrochemical activity, electron transfer, and mechanical stability can be enhanced. At the same time, the loading stability of molecular imprinting can be enhanced, allowing it to maintain corresponding recognition performance during multiple uses and long-term operation.
[0014] Furthermore, the method for modifying the ethylene end groups includes:
[0015] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50-70° C. for 20-30 hours to obtain a precipitate;
[0016] S1-2. The precipitate is washed and dried, and then added to tetrahydrofuran, 3-butene-1-ol and 4-dimethylaminopyridine are added. The product is refluxed at 40-60° C. for 20-30 hours, and then centrifuged, washed, and dried to obtain a glassy carbon electrode modified with an ethylene end group.
[0017] Among them, the addition ratio of glassy carbon electrode, tetrahydrofuran, dichlorothione in S1-1 and tetrahydrofuran, 3-butene-1-ol, 4-dimethylaminopyridine in S1-2 is: 10-30g:300-500ml; 10-20ml:300-500ml:10-30ml:10-30ml.
[0018] Explanation: Modifying the glassy carbon electrode with ethylene end groups improves the electrochemical activity of the electrode surface. Furthermore, through the specific interaction of the ethylene end groups with other molecules, the electrode's selective recognition of specific analytes can be enhanced. The above combination is particularly preferred, resulting in a glassy carbon electrode with a better degradation resistance gene.
[0019] Furthermore, the second electrode is any one of a platinum electrode, a titanium electrode, a glassy carbon electrode, a BDD electrode and a metal oxide electrode.
[0020] Furthermore, the method for loading molecular imprinting on the glassy carbon electrode comprises:
[0021] S1. Place the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes, then add the crosslinker and initiator;
[0022] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0023] Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, crosslinker, and initiator are: 10-30 g of glassy carbon electrode after ethylene end group modification, 200-300 mL of acetonitrile, 100-200 mL of toluene, 10 mmol of template molecule guanine, 1-5 mol of functional monomer methacrylic acid, 100-200 mg of crosslinker, and 10-40 mg of initiator.
[0024] Note: Through the above molecular imprinting loading method, the stability of molecular imprinting loading can be further enhanced through loading conditions, solving the problem of easy detachment of molecular imprinting.
[0025] Furthermore, the molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm.
[0026] Furthermore, the current density of the applied current is: 50-60 mA / cm 2 , the degradation time is 10 to 40 minutes.
[0027] Note: The above current density is more preferred and has a better effect on degrading resistance genes.
[0028] Furthermore, the chemical pollutants are humic acid and its derivatives, glucose and its derivatives, amino acids and their derivatives.
[0029] Furthermore, the antibiotic resistance genes include: tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes and lactam resistance genes.
[0030] The beneficial effects of the present invention are:
[0031] The present invention combines molecular imprinting technology with electrochemical degradation, which can utilize the strong oxidizing effect of the electrochemical degradation process and combine it with the selective function of molecular imprinting technology on resistance genes to achieve efficient degradation of resistance genes in water bodies; at the same time, since the glassy carbon material electrode has the problem of molecular imprinting load falling off from the electrode surface during the electrochemical reaction process, the present invention can form a better structure on the surface of the glassy carbon electrode by loading carbon nanotubes and modifying the ethylene end groups of the glassy carbon electrode, thereby solving the problem of easy falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the molecular imprinting technology principle of the present invention;
[0033] Figure 2 This is a standard curve diagram of the qPCR quantitative detection of resistance genes in the experimental example of the present invention;
[0034] Figure 3 This is a graph showing the degradation efficiency of different ratios of guanine molecules and functional monomer methacrylic acid according to the present invention;
[0035] Figure 4 2 are SEM images of the glassy carbon electrodes of Example 1 and Comparative Example 2 of the present invention;
[0036] Figure 5 1 is an XPS analysis result of the composition elements of the molecularly imprinted glassy carbon electrode according to Example 1 of the present invention;
[0037] Figure 6 is the C1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0038] Figure 7 This is the O1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0039] Figure 8 is the N1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0040] Figure 9 1 is a comparison diagram of the degradation effects of Example 1 and Comparative Example 2 on resistance genes in Example 1 of the present invention;
[0041] Figure 10 is a graph showing the removal rate of resistance genes at different current densities in Example 1 of the present invention;
[0042] Figure 11 1 is a graph showing the removal rate of extracellular resistance genes at different electrolyte concentrations in Example 1 of the present invention;
[0043] Figure 12 is the removal efficiency of the extracellular resistance gene under the two-component system of Example 1 of the present invention;
[0044] Figure 13 This is the kinetic curve of electrochemical oxidation degradation of extracellular resistance genes in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to further illustrate the approach and effects achieved by the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with experiments.
[0046] like Figure 1As shown in Figure 2, molecular imprinting technology enables specific recognition and binding of target molecules by creating cavities in a polymer matrix that match the shape and functional groups of a template molecule. In this process, the template molecule is first mixed with a monomer, and then polymerization is initiated to form a polymer containing the template molecule. The template molecule is then removed from the polymer, leaving behind cavities that complement the template molecule's shape and functional groups. These cavities are able to specifically recognize and bind to the same template molecule, thereby achieving selective capture of the target molecule.
[0047] Example 1: A method for selectively degrading resistance genes in water by electrochemical oxidation, comprising: using a first electrode as an anode and a second electrode as a cathode, applying current to degrade resistance genes in the water;
[0048] Wherein, the first electrode is a molecularly imprinted glassy carbon electrode;
[0049] The molecularly imprinted glassy carbon electrode is obtained by loading a glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and then loading the molecular imprinted electrode. The molecular imprinted electrode is used to selectively identify resistance genes from chemical pollutants in water and bind to the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria, and the second electrode is a platinum electrode. The antibiotic resistance genes include tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes, and beta-lactam resistance genes.
[0050] The method for loading the glassy carbon electrode with carbon nanotubes includes:
[0051] The glassy carbon electrode was polished with metallographic sandpaper, and then polished to a mirror surface on suede with 1.0um, 0.3um and 0.05um Al2O3 polishing powder in sequence, and then cleaned with acetone solution and water ultrasonically.
[0052] The electrode was placed in a deoxygenated 0.03 mg / mL carboxylated carbon nanotube dispersion with a deposition voltage of -1.2 V for 1200 s and a supporting electrolyte of 0.1 mol / L lithium perchlorate to obtain a carbon nanotube-loaded glassy carbon electrode.
[0053] Wherein, the carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent;
[0054] The methods for modifying the ethylene end groups include:
[0055] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 60° C. for 24 hours to obtain a precipitate;
[0056] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 50°C for 24 hours, and then centrifuge, wash, and dry to obtain a glassy carbon electrode modified with an ethylene end group.
[0057] The addition ratio of the glassy carbon electrode, thionyl chloride, and tetrahydrofuran in S1-1 is: 20 g: 15 ml: 400 ml;
[0058] The addition ratio of tetrahydrofuran, 3-butene-1-ol, and 4-dimethylaminopyridine in S1-2 is: 400ml: 20ml: 20ml.
[0059] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0060] S1. Place the glassy carbon electrode modified with vinyl end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; after stirring for 30 minutes, add the crosslinker and initiator (ethylene glycol dimethacrylate as the crosslinker and 2,2'-azobisisobutyronitrile as the initiator);
[0061] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0062] Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linker, and initiator are: 15 g of glassy carbon electrode after ethylene end group modification, 250 mL of acetonitrile, 150 mL of toluene, 10 mmol of template molecule guanine, 3 mol of functional monomer methacrylic acid, 150 mg of cross-linker, and 20 mg of initiator.
[0063] The molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm. The current density of the applied current is 53.08 mA / cm 2 .
[0064] Example 2: The difference between this example and Example 1 is that the second electrode is a titanium electrode; the method for loading the glassy carbon electrode with carbon nanotubes includes: placing the glassy carbon electrode in a 0.02 mg / mL carboxylated carbon nanotube dispersion, setting the voltage to -1 V for deposition, and the deposition time to 1000 s to obtain a carbon nanotube-loaded glassy carbon electrode.
[0065] The methods for modifying the ethylene end groups include:
[0066] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50° C. for 20 hours to obtain a precipitate;
[0067] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 60° C. for 20 h, and then centrifuge, wash, and dry to obtain a glassy carbon electrode modified with an ethylene end group.
[0068] The addition ratio of the glassy carbon electrode, thionyl chloride, and tetrahydrofuran in S1-1 is: 10 g: 10 ml: 300 ml;
[0069] The addition ratio of tetrahydrofuran, 3-butene-1-ol, and 4-dimethylaminopyridine in S1-2 is: 500ml:30ml:30ml.
[0070] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0071] S1. Place the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes, then add the crosslinker and initiator;
[0072] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0073] Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linker, and initiator are: 30 g of glassy carbon electrode after ethylene end group modification, 300 mL of acetonitrile, 100 mL of toluene, 10 mmol of template molecule guanine, 5 mol of functional monomer methacrylic acid, 200 mg of cross-linker, and 40 mg of initiator.
[0074] The current density of the applied current is: 60 mA / cm 2 .
[0075] Embodiment 3: The second electrode is a glassy carbon electrode;
[0076] The method for loading the glassy carbon electrode with carbon nanotubes includes:
[0077] The glassy carbon electrode was placed in a 0.05 mg / mL carboxylated carbon nanotube dispersion, and the voltage was set to -1.2 V for deposition for 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode.
[0078] The methods for modifying the ethylene end groups include:
[0079] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 70° C. for 30 hours to obtain a precipitate;
[0080] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 40°C for 30 hours, and then centrifuge, wash, and dry to obtain a glassy carbon electrode modified with an ethylene end group.
[0081] The addition ratio of the glassy carbon electrode, thionyl chloride, and tetrahydrofuran in S1-1 is: 30 g: 20 ml: 500 ml;
[0082] The addition ratio of tetrahydrofuran, 3-butene-1-ol, and 4-dimethylaminopyridine in S1-2 is: 300 ml: 10 ml: 30 ml.
[0083] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0084] S1. Place the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes, then add the crosslinker and initiator;
[0085] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0086] Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linker, and initiator are: 10 g of glassy carbon electrode after ethylene end group modification, 200 mL of acetonitrile, 200 mL of toluene, 10 mmol of template molecule guanine, 1 mol of functional monomer methacrylic acid, 100 mg of cross-linker, and 10 mg of initiator.
[0087] The current density of the applied current is: 50mA / cm 2 .
[0088] Comparative Example 1: The glassy carbon electrode was not subjected to carbon nanotube loading, ethylene end group modification, or guanine imprinting loading;
[0089] Comparative Example 2: The glassy carbon electrode was only loaded with carbon nanotubes and modified with ethylene end groups, without guanine molecular imprinting loading;
[0090] Comparative Example 3: Only carbon nanotubes were loaded on the glassy carbon electrode without ethylene end group modification or guanine molecular imprinting loading;
[0091] Comparative Example 4: Only guanine molecular imprinting loading was performed on the glassy carbon electrode, without carbon nanotube loading and ethylene end group modification.
[0092] Experimental example:
[0093] 1. Example of degradation effect
[0094] Take the following resistance gene NDM-1 as an example for degradation:
[0095] The acquisition process of the resistance gene NDM-1 is as follows:
[0096] Culture of NDM-1 and plasmid extraction
[0097] LB medium (containing 1.0 g sodium chloride, 0.5 g yeast extract, and 1.0 g peptone per 100 mL of culture medium, and adjusted to pH 7.0-7.2 using 40 g / L sodium hydroxide solution) was prepared, and NDM-1 bacterial suspension and kanamycin sulfate (500 μL of 30 mg / mL kanamycin sulfate and 100 mL of NDM-1 bacterial suspension were added per 100 mL of LB) and cultured overnight in an air bath shaker at 37°C. Plasmids were extracted using the DP105 Rapid Plasmid Miniprep Kit (TIANGEN) and stored in a −21°C refrigerator for later use.
[0098] Molecularly imprinted glassy carbon electrodes specifically degrade extracellular resistance genes
[0099] The degradation reaction was carried out in a beaker. A foam plastic board was used to make a cover to ensure that the electrode spacing was 2 cm. An electrode clamp was used to fix a molecularly imprinted glassy carbon electrode (or a glassy carbon electrode without guanine molecular imprinting in Comparative Example 2) as the anode, a platinum electrode as the cathode, sodium sulfate as the electrolyte, and a DC power supply. The plasmid used was obtained by diluting the plasmid stock solution 500 times. A certain amount of solution in the system was taken out at regular intervals (two parallel samples each time), diluted 1000 times with a 50 mL colorimetric tube, and then a qPCR detection system was configured, and then measured by qPCR.
[0100] qPCR quantitative detection of resistance genes
[0101] The standard curve (CT value and logarithm of ARG absolute abundance) was obtained by serially diluting the plasmid 10-fold. The reaction system was configured using a fluorescence quantitative kit (TIANGEN), and the NDM-1 forward primer (5'
[0102] The primer was a forward primer (3'-CGCCATCCCTGACGATCAAA-3'), and the reverse primer was a reverse primer (3'-CTGAGCACCGCATTAGCCG-5'). The system composition is shown in Table 1 below. The reaction conditions were 40 cycles of pre-denaturation at 95°C for 30 s, denaturation at 95°C for 10 s, annealing at 60°C for 20 s, and extension at 95°C for 15 s.
[0103] Table 1 qPCR reaction system composition
[0104] System composition Dose (μL) TOR 10 NDM-1 forward primer 0.8 NDM-1 reverse primer 0.8 Sterile water 6.4 Samples to be tested 2
[0105] The qPCR standard curve is obtained by diluting the DNA stock solution in a 10-fold gradient, sampling and detecting the CT value by qPCR, and plotting the curve of lgCDNA and CT value. The experimental results are shown in Table 2. The standard curve obtained by fitting the table data is as follows Figure 2 .
[0106] Table 2 qPCR standard curve results
[0107]
[0108] According to the fitting results, we can obtain lgCDNA=-0.25548CT+19.27699, R2=0.98195. Through transformation, we can obtain the calculation formula of DNA copy value, as shown in the following formula (1):
[0109] C DNA =10 -0.25548CT+19.27699 (1)
[0110] The results of subsequent experiments were transformed using this formula.
[0111] The degradation rate was calculated according to formula (2), where c0 represents the initial DNA copy number and c represents the DNA copy number at a specific moment, and the unit is copies / mL.
[0112]
[0113] Experimental results:
[0114] 1. Characterization:
[0115] Characterization and Analysis of Molecularly Imprinted Glassy Carbon Electrodes
[0116] Guanine: MAA (functional monomer methacrylic acid) = 1:5, 2:5, 1:2 and 1:1 (molar ratio), respectively, at a current density of 53.08 mA / cm 2The electrolyte concentration is 0.2M Na2SO4 at room temperature to degrade the extracellular resistance gene. Samples are taken for testing at reaction times of 0min, 10min, 20min and 30min. The removal rate-time curve is drawn after calculation based on the experimental results, as shown in the figure. Figure 3 By comparing the degradation effects of these four electrodes, the optimal preparation conditions were obtained. Figure 3 A comparison shows that the degradation effects of molecularly imprinted glassy carbon electrodes with different ratios on extracellular resistance genes are relatively similar. The degradation rate of the molecularly imprinted glassy carbon electrode (1:1) is relatively slow. The degradation effects of the molecularly imprinted glassy carbon electrode (1:5) and the molecularly imprinted glassy carbon electrode (1:1) are relatively close, but the degradation rate of the former decreases faster after 20 minutes. The molecularly imprinted glassy carbon electrode (1:2) has the highest removal rate of resistance genes at 30 minutes, and maintains a relatively fast rate throughout the reaction. Based on the above analysis, the molecularly imprinted glassy carbon electrode prepared with a guanine to MAA ratio of 1:2 has the best oxidative removal effect on extracellular resistance genes. The molecularly imprinted glassy carbon electrodes mentioned below in this chapter refer to the molecularly imprinted glassy carbon electrode (1:2).
[0117] Morphological analysis of molecularly imprinted glassy carbon electrodes
[0118] The surface morphology of the glassy carbon electrode loaded with molecular imprinting and the glassy carbon electrode without guanine molecular imprinting in comparative example 2 was observed by scanning electron microscopy, as shown below: Figure 4 , which shows the morphology of the molecularly imprinted glassy carbon electrode and the glassy carbon electrode of comparative example 2 without guanine molecular imprinting at different magnifications. When the average particle size is 1 μm, the surface of the molecularly imprinted glassy carbon electrode (c) shows a very rough state with many protrusions and depressions, while the surface of the glassy carbon electrode of comparative example 2 without guanine molecular imprinting is relatively flat, without too many protrusions and depressions, and is displayed as a block-like staggered distribution. When the average particle size is 100 nm, the surface of the molecularly imprinted glassy carbon electrode (a) shows a larger concave portion, similar to a channel, while the surface of the glassy carbon electrode of comparative example 2 without guanine molecular imprinting is relatively full and has no structure similar to a hole. Through comprehensive analysis of the surface morphology and the structure of the molecularly imprinted glassy carbon electrode, it was found that guanine was added as a template molecule during the preparation of the molecularly imprinted glassy carbon electrode and then the guanine in the polymer was washed away by hydrochloric acid, leaving a specific imprint of guanine. This should leave multiple guanine-imprinted holes on the surface of the electrode material, which is consistent with the surface morphology observed by SEM ( Figure 4As for the glassy carbon electrode without guanine molecular imprinting in comparative example 2, the preparation process is different from that of the glassy carbon electrode loaded with molecular imprinting, except that guanine is not added as a template molecule. Therefore, in terms of surface morphology, compared with the glassy carbon electrode loaded with molecular imprinting, there are no specific pores of guanine molecular imprinting, and only the state of polymer covering the surface is shown, so the surface is smooth with fewer pores, which is consistent with the surface morphology observed by SEM ( Figure 4 b) and d) in the above are consistent.
[0119] Elemental Analysis of Molecularly Imprinted Glassy Carbon Electrode
[0120] The experiment used XPS to analyze the composition elements of the molecularly imprinted glassy carbon electrode. Figure 5 ) analysis. It was determined that the molecularly imprinted glassy carbon electrode is primarily composed of C, O, N, and S. The quantified percentages of these elements are shown in Table 3. A comparison of the four elements reveals the following distribution: C > O > N > S, with C being the primary component and N and S present in very low concentrations.
[0121] Table 3 Element content analysis
[0122]
[0123] Observe the C1s narrow spectrum ( Figure 6 ) The curve is relatively smooth, with a peak at a bond energy of 284.80 eV. Peak fitting revealed that the C in the molecularly imprinted glassy carbon electrode exists mainly as CC, followed by CO, and C=O is the least. Figure 7 ), it can be found that the curve is relatively smooth, slightly rough, with a main peak, but the main peak has a certain bifurcation, divided into three small peaks, located at binding energies of 531.28eV, 531.68eV, and 531.88eV, respectively, with peaks located at 531.68eV and 531.88eV. After peak fitting, it was found that the main form of O in the molecularly imprinted glassy carbon electrode is C=O, and a small amount of CO is also present. Observing the N1s narrow spectrum ( Figure 8 ) The curve is not smooth and has many spikes, indicating that the N content is low or unevenly distributed, and the content of this element is relatively low within the range of the tested samples. The two peaks are located at 400.38eV and 400.88eV. After peak fitting processing, it is found that the existence form of N is C-NH2. In the process of material preparation, six elements, C, H, O, S, Cl, and N, are mainly involved. In the XPS analysis, there are three elements, C, O, N, and S (XPS cannot detect H element). It is speculated that the reaction is relatively complete during the material synthesis process. There is very little N element, indicating that the guanine (C5H5N5O) in the molecularly imprinted glassy carbon electrode is almost completely washed away by hydrochloric acid, leaving the specific molecular imprint of guanine.
[0124] Analysis of extracellular resistance genes by selective electrochemical degradation using molecularly imprinted glassy carbon electrodes
[0125] The efficiency of electrochemical oxidation degradation of extracellular resistance genes by the optimized molecularly imprinted glassy carbon electrode was compared with that of the glassy carbon electrode without guanine molecular imprinting in comparative example 2 and the unmodified glassy carbon electrode (G) in comparative example 3 to study the advantages of the molecularly imprinted glassy carbon electrode in specifically degrading extracellular resistance genes. The results are as follows Figure 9 . By comparing the curves, it can be found that the three types of glassy carbon electrodes loaded with molecular imprinting as the effect of anode electrochemical oxidation degradation of extracellular resistance genes are>comparative example 3 ordinary glassy carbon electrode (G)>comparative example 2 glassy carbon electrode without guanine molecular imprinting loading. Since the surface of the glassy carbon electrode loaded with molecular imprinting contains guanine molecular imprinting specific recognition sites, it can increase the movement of resistance genes in the electrolyte solution to the anode surface, thereby enabling the free radicals generated at the anode to undergo oxidation reaction with the resistance genes, thereby accelerating the removal of resistance genes. The glassy carbon electrode without guanine molecular imprinting loading in comparative example 2 is not as effective in removing resistance genes as the unmodified ordinary glassy carbon electrode (G). This may be because the surface of the glassy carbon electrode without guanine molecular imprinting loading in comparative example 2 is wrapped by a large amount of polymer, which relatively reduces the effective surface area of the anode, resulting in a decrease in the electrochemical oxidation effect, and the degradation effect is not as good as that of the unmodified glassy carbon electrode. Specifically, the degradation test results at 30 minutes are shown in Table 4 below:
[0126] Table 4 Effects of different treatments on the degradation of resistance genes
[0127] parameter Degradation rate (%) Comparative Example 1 54.54 Comparative Example 2 66.12 Comparative Example 3 76.06 Comparative Example 4 77.04 Example 1 88.73
[0128] Using the glassy carbon electrodes of Example 1 and Comparative Example 4 that were recovered after the explanation, after secondary degradation, the degradation change rate of Example 1 (the ratio of the difference between the two degradation rate changes to the first degradation rate) was 3-5%, while the degradation change rate of Comparative Example 4 was 45-60%. It can be seen that the molecular imprinting load in Comparative Example 4 is unstable and very easy to fall off, while that in Example 1 of the present invention is relatively stable.
[0129] Effect of current density on electrochemical oxidation effect
[0130] This experiment uses a constant current regulated power supply. By adjusting the current value (20mA, 40mA, 50mA, 60mA), different current densities (surface area of the molecularly imprinted glassy carbon electrode = 0.942cm 2 , the current density is 21.23 mA / cm 2 , 42.46mA / cm 2 , 53.08mA / cm 2 、63.69mA / cm2 ), the experimental results are as follows Figure 10 The results show that increasing the current density can effectively improve the removal rate of extracellular resistance genes, but when the current density is 63.69 mA / cm 2 When the degradation efficiency is improved, the effect is not significant compared to 53.08 mA / cm2, and the degradation efficiency is not as good as 53.08 mA / cm2 at 30 min. 2 Increasing the current density can increase the production of OH, etc., but at too high a current density, it will lead to an increase in side reactions. Therefore, a comprehensive analysis of energy consumption and removal efficiency is presented in Table 5. From the data in Table 5, it can be seen that the current density is 53.08 mA / cm 2 When the energy consumption increases, the removal rate of extracellular resistance genes increases significantly. However, further increasing the current not only increases the energy consumption but also reduces the removal rate. Therefore, the optimal current density is determined to be 53.08 mA / cm 2 .
[0131] Table 5 Comprehensive analysis of degradation of extracellular resistance genes at different current densities
[0132]
[0133] Effect of electrolyte concentration on electrochemical oxidation effect
[0134] The electrolyte in this experiment is sodium sulfate solution, and different concentrations of sodium sulfate solution are prepared (0.1M, 0.2M, 0.3M, 0.4M respectively). The experimental results are as follows Figure 11 . Analysis of the experimental results shows that when the electrolyte concentration is low, the removal rate of extracellular resistance genes increases with the increase of electrolyte concentration. However, when the electrolyte concentration increases to 0.5M, the resistance gene removal rate decreases instead. The efficiency and energy consumption analysis under different electrolyte concentrations are shown in Table 6 below. It can be seen from the data in Table 6 that increasing the electrolyte concentration can also reduce the consumption of electrical energy. As the electrolyte concentration increases, the collisions between ions in the reaction system increase, but if the concentration is too high, the electrolyte will be adsorbed on the electrode surface, hindering the migration of pollutants to the electrode surface and reducing the chance of pollutants reacting with reactive groups near the electrode. Taking all factors into consideration, the optimal Na2SO4 concentration is 0.4M.
[0135] Table 6 Comprehensive analysis of the removal rate of extracellular resistance genes under different electrolyte concentrations
[0136] Electrolyte concentration Current (mA) Voltage (V) Energy consumption (kWh) Degradation rate (%) 0.1M 50 5.2 0.94 71.61 0.2M 50 4.1 0.74 75.63 0.3M 50 3.2 0.58 80.05 0.4M 50 2.9 0.52 93.70 0.5M 50 2.7 0.49 80.81
[0137] Selective study of molecularly imprinted glassy carbon electrodes for resistant gene degradation
[0138] The previous experiments all considered the degradation of extracellular resistance genes under single component conditions. This section mainly studies the selective electrochemical oxidation performance of extracellular resistance genes by the molecularly imprinted glassy carbon electrode in the eARGs+10mg / L humic acid system, eARGs+40mg / L glucose system, and eARGs+20mg / L amino acid system. This experiment was conducted at a current density of 53.08mA / cm 2 The experimental results are shown in Figure 2. Figure 12 As shown in the figure, the results show that the removal efficiency of extracellular resistance genes decreased slightly in both two-component systems, but within a 30-minute reaction time, a removal rate exceeding 60% was achieved. The presence of other components hindered the mass transfer of resistance genes and competed with them for free radicals, resulting in a decrease in the removal efficiency. When the components consisted of eARGs plus 10 mg / L humic acid, humic acid had little effect on the degradation efficiency of extracellular resistance genes by the molecularly imprinted glassy carbon electrode, retaining 88.90%. Glucose and amino acids had a slightly greater impact on the removal of extracellular resistance genes, but the degradation rates remained at 73.31% and 78.31% respectively. Further extension of the reaction time resulted in even higher removal rates for extracellular resistance genes. Overall, the molecularly imprinted glassy carbon electrode possesses the ability to selectively electrochemically oxidize and degrade extracellular resistance genes.
[0139] Reaction kinetics studies
[0140] The kinetic study was conducted under the condition of single component of extracellular resistance gene, and the sampling time points were 0min, 10min, 20min, 30min, 40min and 60min. The experimental data were processed and the Ln(C / C0)-Reactiontime curve was drawn as follows Figure 13 . Figure 13 It shows that Ln(C / C0) has a good linear relationship with the reaction time. The reaction process of electrochemical oxidation degradation of extracellular resistance genes by the molecularly imprinted glassy carbon electrode conforms to the first-order kinetic equation, R2=0.97603, and the kinetic equation is c=c0e-0.05691t. The reaction rate constant k=0.05691min-1. By performing first-order kinetic fitting on the ordinary glassy carbon electrode and the glassy carbon electrode of comparative example 2 without guanine molecular imprinting loading, the rate constants are k1=-0.04749 (R2=0.99714) and k2=-0.03946 (R2=0.99559), respectively. It can be obtained that k>k1>k2, and the molecularly imprinted glassy carbon electrode has the maximum reaction rate. The results of the present invention effectively improve the efficiency of resistance gene removal.
Claims
1. A method for selectively degrading resistance genes in water by electrochemical oxidation, characterized in that: include: With the first electrode as the anode and the second electrode as the cathode, current is applied to degrade the resistance genes in the water; Wherein, the first electrode is a molecularly imprinted glassy carbon electrode; The molecularly imprinted glassy carbon electrode is obtained by loading a glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and loading the molecular imprint. The molecular imprint is used to selectively identify resistance genes from chemical pollutants in water and bind to the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria.
2. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The method for loading carbon nanotubes on a glassy carbon electrode comprises: The glassy carbon electrode was placed in a carboxylated carbon nanotube dispersion and deposited at a set voltage of -1 to -1.2 V for a deposition time of 1000 to 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode. The carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent, and the concentration of the carboxylated carbon nanotube dispersion is 0.02-0.05 mg / mL.
3. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 2, characterized in that: The method for modifying the ethylene end groups comprises: S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50-70° C. for 20-30 hours to obtain a precipitate; S1-2. The precipitate is washed and dried, and then added to tetrahydrofuran, 3-butene-1-ol and 4-dimethylaminopyridine are added. The product is refluxed at 40-60° C. for 20-30 hours, and then centrifuged, washed, and dried to obtain a glassy carbon electrode modified with an ethylene end group. Among them, the addition ratio of glassy carbon electrode, tetrahydrofuran, dichlorothione in S1-1 and tetrahydrofuran, 3-butene-1-ol, 4-dimethylaminopyridine in S1-2 is: 10-30g:300-500ml; 10-20ml:300-500ml:10-30ml:10-30ml.
4. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The second electrode is any one of a platinum electrode, a titanium electrode, a glassy carbon electrode, a BDD electrode, and a metal oxide electrode.
5. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 3, characterized in that: The method for loading molecular imprinting comprises: S1. Place the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes, then add the crosslinker and initiator; S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode; Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, crosslinker, and initiator are: 10-30 g of glassy carbon electrode after ethylene end group modification, 200-300 mL of acetonitrile, 100-200 mL of toluene, 10 mmol of template molecule guanine, 1-5 mol of functional monomer methacrylic acid, 100-200 mg of crosslinker, and 10-40 mg of initiator.
6. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm.
7. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The current density of the applied current is: 50~60mA / cm 2 .
8. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The degradation time is 10 to 40 minutes.
9. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The compound pollutants are humic acid and its derivatives, glucose and its derivatives, amino acids and their derivatives.
10. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The antibiotic resistance genes include tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes and lactam resistance genes.
Citation Information
Patent Citations
Selective separation of heavy metal ion using the metalion imprinted polymer(MIIP)
KR100723919B1
Preparation method for modified carbon nanotube, preparation method for electrode, and use of electrode in salt lake lithium extraction
WO2024197577A1